Using a participatory approach to identify priorities to advance LHS implementation at an academic medical center - Reid M. Eagleson; Madeline Gibson; Carletta Dobbins; Frederick Van Pelt; Allyson Hall; Larry Hearld; Andrea L. Cherrington; Jacob McMahon; Keith Tony Jones; Michael J. Mugavero (Learning Health Systems)
Abstract Introduction Like many other academic medical centers, the University of Alabama at Birmingham (UAB) aspires to adopt learning health system (LHS) principles and practices more fully. Applying LHS principles establishes a culture where clinical and operational practices constantly generate questions and leverage information technology (IT) and methodological expertise to facilitate systematic evaluation of care delivery, health outcomes, and the effects of improvement initiatives. Despite the potential benefits, differences in priorities, timelines, and expectations spanning an academic medical center's clinical care, administrative operations, and research arms create barriers to adopting and implementing an LHS. Methods UAB's Center for Outcomes and Effectiveness Research and Education, in partnership with UAB Medicine's Department of Clinical Practice Transformation, applied part of the Precision Problem Solving methodology to advance the implementation of LHS principles at UAB. Results Sixty‐two stakeholders across the UAB health system and academic schools noted 131 concerns regarding the development of an LHS at UAB. From the 131 items, eight major themes were identified, named, and prioritized through a series of focus groups. Of the eight major themes, “Creating a Structure for Aligned and Informed Prioritization” and “Right Data, Right Time, Improved Performance” ranked in the top three most important themes across all focus groups and became the critical priorities as UAB enhances its LHS. A task force comprised of diverse constituents from across UAB's academic medical center is taking first steps toward addressing these priority areas. Initial funding supports a prototype for enhanced health system data access and pilot projects conducted by researchers embedded in health system teams. Conclusion We suggest that our experience conducting a deliberate process with broad engagement across both the health system and academic arms of the university may be informative to others seeking to advance LHS principles at academic health centers across a myriad of settings.